2016
DOI: 10.1039/c6cy01051b
|View full text |Cite
|
Sign up to set email alerts
|

Study of short-lived and early reaction intermediates in organocatalytic asymmetric amination reactions by ion-mobility mass spectrometry

Abstract: Reactive solvent-assisted eletrosrpay ionization coupled to ion-mobility mass spectrometry (reactive SAESI-IM-MS) was used to study the reactive intermediates in the organocatalytic asymmetric amination reaction. The transient intermediates including two isomers of carbinolamine and iminium species in the early stage of the enamine formation and previously unrecognized triazane species appearing before iminium intermediates 6 formation were successfully intercepted and characterized by reactive-SAESI-IM-MS. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
0
13
1
Order By: Relevance
“…Nevertheless, the veracity of these assumptionss till hast ob ea ddressedt os hed light on the overall organocatalytic sequence;t his is ar equisite endeavor to broaden the scope of this useful organocatalytic process and to tackle,e ventually,a ne fficaciousa symmetric version. Recently,t he coupling of the ion mobility spectrometry (IMS) technique with MS not only afforded an ew dimensionf or the separation of closely relateds tructures within challengingc omplexm ixtures [9][10][11] but also provided novel opportunities to determine three-dimensional structures. The softness of ESI permitst he "fishing" of charged and labile synthetic intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the veracity of these assumptionss till hast ob ea ddressedt os hed light on the overall organocatalytic sequence;t his is ar equisite endeavor to broaden the scope of this useful organocatalytic process and to tackle,e ventually,a ne fficaciousa symmetric version. Recently,t he coupling of the ion mobility spectrometry (IMS) technique with MS not only afforded an ew dimensionf or the separation of closely relateds tructures within challengingc omplexm ixtures [9][10][11] but also provided novel opportunities to determine three-dimensional structures. The softness of ESI permitst he "fishing" of charged and labile synthetic intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] This is a salient feature to tackle the determination of heat-sensitive speciess uch as the ones putatively encountered from Meldrum's acid (1)( e.g., 4 and 5). [7,10,14] We are pleased to report am echanistic investigation of the (3 + 2) annulation reaction between Meldrum's acid (1a)a nd N-benzyl nitrone 2a allowing unprecedented insighti nto this useful albeit complex organocatalyzed domino process thanks to the powerfulness of ac ombination of real-time reaction monitoring by ESI-IMS-MS with DFT computations. [12] In IMS, ions are separated as af unctiono ft heir charge,s hape, and size throught heir collisionc ross-section (CCS, W).…”
Section: Introductionmentioning
confidence: 99%
“…Another example, how ion mobility separation can add another dimension to mass-spectrometric investigation of reaction intermediates comes from the group of Guo. 42 They studied intermediates formed in an organocatalytic reaction developed for C-N couplings. 1 This type of reactions is well suited for mass spectrometry investigation, because the intermediates are either charged iminium ions (e.g., I 2 in Fig.…”
Section: Beyond Mass-analysis: Ion Mobility Separationmentioning
confidence: 99%
“…SAESI‐MS allows timesaving, no heating and less solvent consumption. Several applications of various nonpolar or low‐polarity solvent systems have been demonstrated by SAESI‐MS …”
Section: Introductionmentioning
confidence: 99%
“…When the sample is a liquid, continuous injection, continuous monitoring and continuous analysis are often necessary, and an analytical strategy based on the atmospheric pressure chemical ionization (APCI) and electrospray ionization (ESI) mass spectrometry mechanism is appropriate. However, nonpolar or low-polarity solvents extracts, such as petroleum ether extracts, are difficult to analyze applications of various nonpolar or low-polarity solvent systems have been demonstrated by SAESI-MS. 22,[24][25][26] In the study reported here we attempted to perform the direct…”
Section: Introductionmentioning
confidence: 99%